Stakeholder-engaged research is necessary across the criminal-legal spectrum. Issue 1 (15th November 2023) - Wurcel, Alysse G.; Kraus, Christina; Johnson, O'Dell; Zaller, Nicholas D.; Ray, Bradley; Spaulding, Anne C.; Flynn, Tara; Quinn, Cynthia; Day, Ronald; Akiyama, Matthew J.; Del Pozo, Brandon; Meyer, Fred; et al.
Abstract: People with lived experience of incarceration have higher rates of morbidity and mortality compared to people without history of incarceration. Research conducted unethically in prisons and jails led to increased scrutiny of research to ensure the needs of those studied are protected. One consequence of increased restrictions on research with criminal-legal involved populations is reluctance to engage in research evaluations of healthcare for people who are incarcerated and people who have lived experience of incarceration. Ethical research can be done in partnership with people with lived experience of incarceration and other key stakeholders and should be encouraged. In this article, we describe how stakeholder engagement can be accomplished in this setting, and further, how such engagement leads to impactful research that can be disseminated and implemented across disciplines and communities. The goal is to build trust across the spectrum of people who work, live in, or are impacted by the criminal-legal system, with the purpose of moving toward health equity.